Audit Quality Of Telecommunication And Providers Sector Companies Listed On The Indonesia Stock Exchange In 2021-2023 - Ismawati, Kun; Setiawan, Iwan; Gunardi, Effendy (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study aims to determine the effect of managerial ownership, audit committee, and auditor turnover on audit quality. The population used is telecommunications sector companies and providers listed on the Indonesia Stock Exchange for the 2021-2023 period. The sample used was 63 data from 21 telecommunications sector companies and providers listed on the Indonesia Stock Exchange for the 2021-2023 period, with a sampling technique of purposive sampling or using certain considerations and criteria. The data analysis techniques used were descriptive statistical analysis, logistic regression analysis, determination coefficient test (R2), t-test, and F-test. The result’s research stated that the managerial ownership variable has a significant effect on audit quality with a significant value of 0.024. The audit committee variable has a significant effect on audit quality with a significant value of 0.041. The auditor turnover variable has a significant effect on audit quality with a significant value of 0.008. Simultaneously, the three independent variables (managerial ownership, audit committee, and auditor turnover) have a significant effect on audit quality.